#### Solve simultaneous linear equations:

(i) 9x^{2} + 12x + 4 – 16y^{2}

(ii) x^{4} + 3x^{2} + 4

**Solution:**

(i) 9x^{2} + 12x + 4 – 16y^{2}

Above terms can be written as,

(3x)^{2} + (2 × 3x × 2) + 2^{2} – 16y^{2}

Then, (3x + 2)^{2} – (4y)^{2}

(3x + 2 + 4y) (3x + 2 – 4y)

(ii) x^{4} + 3x^{2} + 4

x^{4} + 3x^{2} + 4

Above terms can be written as,

(x^{2})^{2} + 3(x^{2}) + 4

(x^{2})^{2} + (2)^{2} + 4x^{2} – x^{2}

(x^{2} + 2)^{2} – (x^{2})

We know that, (a^{2} – b^{2}) = (a + b) (a – b)

(x^{2} + 2 + x) (x^{2} + 2 – x)

(x^{2} + x + 2) (x^{2} – x + 2)

**More Solutions:**

- Solve the following systems of simultaneous linear equations.
- Solve the following pairs of linear equations.
- Solve simultaneous linear equations: (i) 2/x + 2/3y = 1/6
- Solve simultaneous linear equations: (i) (7x – 2y)/ xy = 5
- Solve simultaneous linear equations: (i) 3x + 14y = 5xy
- Solve simultaneous linear equations: (i) 20/ (x + 1) + 4/ (y – 1) = 5
- Solve simultaneous linear equations: (i) 1/ 2(2x + 3y) + 12/ 7(3x – 2y) = ½
- If r = 3, y =k is a solution of the equation 3x – 4y +7 = 0
- If x = a, y = b is the solution of the equations x -y = 2 and x + y = 4.